The Effect of Operating Conditions of Urea Dewaxing on the Pour Point of Light Lubricating Oil - A.Mohammed, Abdul-Halim; S.Akram, Noor (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
An investigation was conducted for dewaxing of lubricating oil fraction by urea to reduce the pour point.In this study mixture of 45 % methyl ethyl ketone (MEK) and 55 % toluene was used as a solvent. The studied variables are mixing time (10-70 min), solvent to oil volume ratio (0.5:1- 2:1), urea to wax weight ratio (2- 6) and constant mixing speed 1500 rpm. By analysis of the experimental results, the best operating conditions achieved are mixing time 40 min, solvent/oil 2:1 volume ratio, and urea/wax 4:1 weight ratio. At these conditions the pour point of the lubricating oil decreases from 24 ° C to -13 °C.